PENEGAKAN HUKUM DALAM SYARI’AT ISLAM (UINSI Samarinda, 2013)
Application of the rule of law at the beginning of Islam, in principle, in the hands of the Prophet, given the Qur'an as a guide and guide of human life. Being al-Hadith (Prophet's deeds) as explanatory of the Qur'an. Indeed the Prophet established the law is the law of God, because God ordered him to follow what they're told and leave what the Prophet prohibited. Principles of justice in Islam contains valuable concept. He is not synonymous with man-made justice. Humanism human fairness doctrine has alienated transcendental values and have glorified human beings as individuals, so that man becomes a central point. Speaking about the rule of law in Islam, the author tries to link it with the application of punishment in Islam, which is the concept discussed in the chapter jinayah fiqh.